Improving the Odds in Advanced Breast Cancer With Combination Immunotherapy: Stepwise Addition of Vaccine, Immune Checkpoint Inhibitor, Chemotherapy, and HDAC Inhibitor in Advanced Stage Breast Cancer - Gatti-Mays, Margaret E.; Gameiro, Sofia R.; Ozawa, Yohei; Knudson, Karin M.; Hicks, Kristin C.; Palena, Claudia; Cordes, Lisa M.; Steinberg, Seth M.; Francis, Deneise; Karzai, Fatima; Lipkowitz, Stanley; Donahue, Renee N.; et al. (Frontiers in Oncology, 2021)
Breast tumors commonly harbor low mutational burden, low PD-L1 expression, defective antigen processing/presentation, and an immunosuppressive tumor microenvironment (TME). In a malignancy mostly refractory to checkpoint blockade, there is an unmet clinical need for novel combination approaches that increase tumor immune infiltration and tumor control. Preclinical data have guided the development of this clinical trial combining 1) BN-Brachyury (a poxvirus vaccine platform encoding the tumor associated antigen brachyury), 2) bintrafusp alfa (a bifunctional protein composed of the extracellular domain of the TGF-βRII receptor (TGFβ “trap”) fused to a human IgG1 anti-PD-L1), 3), entinostat (a class I histone deacetylase inhibitor), and 4) T-DM1 (ado-trastuzumab emtansine, a standard of care antibody-drug conjugate targeting HER2). We hypothesize that this tetratherapy will induce a robust immune response against HER2+ breast cancer with improved response rates through 1) expanding tumor antigen-specific effector T cells, natural killer cells, and immunostimulatory dendritic cells, 2) improving antigen presentation, and 3) decreasing inhibitory cytokines, regulatory T cells, and myeloid-derived suppressor cells. In an orthotopic HER2+ murine breast cancer model, tetratherapy induced high levels of antigen-specific T cell responses, tumor CD8+ T cell/Treg ratio, and augmented the presence of IFNγ- or TNFα-producing CD8+ T cells and IFNγ/TNFα bifunctional CD8+ T cells with increased cytokine production. Similar effects were observed in tumor CD4+ effector T cells. Based on this data, a phase 1b clinical trial evaluating the stepwise addition of BN-Brachyury, bintrafusp alfa, T-DM1 and entinostat in advanced breast cancer was designed. Arm 1 (TNBC) receives BN-Brachyury + bintrafusp alfa. Arm 2 (HER2+) receives T-DM1 + BN-Brachyury + bintrafusp alfa. After safety is established in Arm 2, Arm 3 (HER2+) will receive T-DM1 + BN-Brachyury + bintrafusp alfa + entinostat. Reimaging will occur every 2 cycles (1 cycle = 21 days). Arms 2 and 3 undergo research biopsies at baseline and after 2 cycles to evaluate changes within the TME. Peripheral immune responses will be evaluated. Co-primary objectives are response rate and safety. All arms employ a safety assessment in the initial six patients and a 2-stage Simon design for clinical efficacy (Arm 1 if ≥ three responses of eight then expand to 13 patients; Arms 2 and 3 if ≥ four responses of 14 then expand to 19 patients per arm). Secondary objectives include progression-free survival and changes in tumor infiltrating lymphocytes. Exploratory analyses include changes in peripheral immune cells and cytokines. To our knowledge, the combination of a vaccine, an anti-PD-L1 antibody, entinostat, and T-DM1 has not been previously evaluated in the preclinical or clinical setting. This trial (NCT04296942) is open at the National Cancer Institute (Bethesda, MD).